The Hollow - Roberts, Nora (Roberts, Nora. Sign of seven trilogy, 2019)
As the madness, which happens for seven days every seven years, prepares to descend upon the town of Hawkins Hollow, three men bound by blood and three woman bound by ancestry to a demon join forces to stop the terror from beginning again.